Minimally invasive biomarker confirms glial activation present in Alzheimer's disease: a preliminary study - Tran T (Dove Medical Press, 2011)
Napapon Sailasuta, Kent Harris, Thao Tran, Brian RossClinical MR Unit, Huntington Medical Research Institutes, Pasadena, CA, USAAbstract: We applied 13C magnetic resonance spectroscopy (MRS), a nonradioactive, noninvasive brain imaging technique, to quantify the oxidation of [1-13C] acetate in a conventional clinical magnetic resonance imaging (MRI) scanner in five consecutive elderly subjects at various clinical stages of Alzheimer's disease (AD) progression. [1-13C] acetate entered the brain and was metabolized to [5-13C] glutamate and glutamine, as well as [1-13C] glutamate and glutamine, and the final glial oxidation product, 13C bicarbonate, at a linear rate. Calculation of the initial slope was similar in a single subject, examined twice, 1 month apart (test-re-test 8%). Mean rate of cerebral bicarbonate production in this elderly group was 0.040 ± 0.01 (n = 5). Assuming that the rate of conversion of acetate to bicarbonate is a reflection of glial metabolic rate and that glial metabolic rate is a surrogate marker for 'neuroinflammation', our preliminary results suggest that [1-13C] MRS may provide biomarkers for diseases, believed to involve microglia and other cells of the astrocyte series. Among these is AD, for which novel drugs which ameliorate the damaging effects of neuroinflammation before symptoms of dementia appear, are in advanced development. The value of 13C MRS as an early, noninvasive biomarker may lie in the conduct of cost-effective clinical trials.Keywords: Alzheimer's disease, noninvasive biomarker, glial activation